Research on the cultivation of green competitiveness among chinese heavily polluting enterprises under country/district environmental regulations - Zhang, Tongjian; Zho, Jian-ya; Hussain, Rana Yassir; Wang, Min; Ren, Kai (Frontiers in Environmental Science, 2022)
The development of the world economy has caused serious environmental pollution, which has resulted in an ecological crisis. With the acceleration of economic development, China’s ecological crisis is becoming more serious. Green technology innovation is an important driving force in realizing green economic development, and heavily polluting enterprises are the key link to cultivating green technology innovation. The Porter hypothesis holds that environmental regulation has a promoting effect on enterprises’ green technology innovation, but this is not reflected in the context of China. As a basic administrative unit, the implementation of environmental regulations in counties and districts determines the effectiveness of environmental policies. Utilizing structural equation modeling, this study analyzes the cultivation of the green technology innovation ability of heavily polluting enterprises under environmental regulations. The results show that command-based environmental regulation can effectively promote enterprises’ green technology innovation ability. Incentive-based environmental regulation needs to be strengthened to drive the development of enterprises’ “three wastes” treatment innovation ability. Voluntary environmental regulation does not effectively promote green process innovation and “three wastes” treatment innovation. In addition, enterprises’ current “three wastes” treatment innovation capacity is not enough to promote the improvement of enterprises’ green competitiveness. The results of this article show that environmental regulation is conducive to the green innovation ability of enterprises, and this promotion effect needs to be further strengthened. Moreover, the highlighted research limitations will contribute to the subsequent research work.